Documenting green hotel practices at The Apurva Kempinski Bali - I Ketut Alit Widiana; I Ketut Astawa; Ni Nyoman Triyuni; Indah Utami Chaerunnisah (Politeknik Negeri Bali, 2022)
This research aimed to find out the documentation of green hotel practices implemented by The Apurva Kempinski Bali, Indonesia, based on the indicators developed by Earth Check known as 10 key performance areas for hotel-accommodation business. Methods of data collection used are by conducting interviews with key and supporting informants, observation techniques using participant observation, literature review, and document study. The data analysis method used is qualitative research through transcript data, data reduction, data displaying, and concluding. The result of this research shows that The Apurva Kempinski Bali has fulfilled the requirements of the certification and has applied the green hotel practices within the hotel area to support sustainable developments including energy efficiency, freshwater resources, waste-water management, solid waste management, ecosystem and conservation, land use planning, air quality protection, management of social and cultures, and harmful substances management. Some improvements need to be taken into account such as the renewable energy generation potential evaluation, shower, and taps low flow installation, and sustainable room amenities materials. It is a critical and important advantage for the hotel as well to attract more guests to stay, since the topic of sustainability nowadays has become famous which affecting the decision of guest to staying in the hotel. This paper is focusing on the documentation of green hotel practices that has been implemented by The Apurva Kempinski Bali in order to support sustainable development goals.